2015
DOI: 10.1007/s00259-015-2997-6
|View full text |Cite
|
Sign up to set email alerts
|

18F-Fluorocholine PET/CT as a complementary tool in the follow-up of low-grade glioma: diagnostic accuracy and clinical utility

Abstract: Our results support the need to complement structural MRI with aMRI and nuclear medicine procedures in selected patients. (18)F-Fluorocholine PET/CT can be useful in the individualized management of patients with treated LGG with uncertain clinical and/or radiological evidence of tumour activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…Using TBR, the reported diagnostic accuracy is even higher because TBR is significantly higher in patients with TP with respect to negative cases 9,20,21 . On the other hand, 18 F-fluorocholine seems to offer the same results, based on its capability to predict therapy response 10,22 . Similarly to the previously reported results by Montes et al, 20 our mean SUV max and TBR values significantly differed between TP and negative cases.…”
Section: Discussionsupporting
confidence: 75%
“…Using TBR, the reported diagnostic accuracy is even higher because TBR is significantly higher in patients with TP with respect to negative cases 9,20,21 . On the other hand, 18 F-fluorocholine seems to offer the same results, based on its capability to predict therapy response 10,22 . Similarly to the previously reported results by Montes et al, 20 our mean SUV max and TBR values significantly differed between TP and negative cases.…”
Section: Discussionsupporting
confidence: 75%
“…It is worth noting that no such false positive being observed in Ref. [ 12 ] based on patient-specific studies. This difference may be caused by the in vivo environment of each patient, the location, growth stage and dimension of the tumor, and PET scanner, etc.…”
Section: Discussionmentioning
confidence: 91%
“…Only 18 F-FCH provides a clear contrast between tumor and normal cerebral tissues ( Fig 1D ). It is observed that normal cerebral tissues typically represent low 18 F-FCH uptake [ 12 ] as shown in Fig 2A . However, in some of the control animals, 18 F-FCH uptake is unexpectedly observed in normal brain tissue ( Fig 2B ), resulting in potential false-positive findings.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study by Gómez-Río and colleagues demonstrated that 18 F-fluorocholine PET/CT is useful to detect a recurrence of posttreatment LGG [3]. The value of this study is that the study was prospectively done in comparison with standard/ advanced radiological examinations performed with clinically available procedures at present.…”
mentioning
confidence: 98%